2009
DOI: 10.1017/s1751731109990279
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic associations between reproduction and production traits based on a sire and dam line with common ancestry

Abstract: Genetic parameters for survival, reproduction and production traits were estimated for a sire and dam line, originating from one Large White breed separated more than 25 years ago. The change in parameters due to different selection pressure on reproduction and production traits in both lines was also examined. Data collected between 1990 and 2007 were available for the analysis of reproduction traits in 4713 litters (sire line) and 14 836 litters (dam line) and for the production traits in 58 329 pigs (sire l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
13
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
5
13
1
Order By: Relevance
“…On the other hand, (Hermesch et al 2000;Chen et al 2003;Holm et al 2004) have reported low (and antagonistic) genetic correlations between production and reproductive traits. This is in agreement with Arango et al (2005) and Kapell et al (2009), who reported relatively high antagonistic correlations. A general problem in comparing studies of growth traits of pigs is the substantial diversity in definition of growth traits.…”
Section: Pigssupporting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, (Hermesch et al 2000;Chen et al 2003;Holm et al 2004) have reported low (and antagonistic) genetic correlations between production and reproductive traits. This is in agreement with Arango et al (2005) and Kapell et al (2009), who reported relatively high antagonistic correlations. A general problem in comparing studies of growth traits of pigs is the substantial diversity in definition of growth traits.…”
Section: Pigssupporting
confidence: 92%
“…The proportion of variance due to the service sire was very low (between 0.8 and 1.6%). Similar low heritabilities have been reported by other authors (Serenius et al 2003;Su et al 2007;Kapell et al 2009;Chen et al 2010). A general question is whether selection against piglet losses may be effective.…”
Section: Pigssupporting
confidence: 87%
“…Very low genetic correlations between litter size traits on the one hand and growth rate or lean meat content (backfat thickness) on the other were reported by several authors (Noguera et al, 2002;Arango et al, 2005;Kapell et al, 2009). However, litter size and production and quality traits are probably not independent as shown in a selection experiment by Estany et al (2002a, b).…”
Section: Discussionmentioning
confidence: 90%
“…The present study was focused on the behaviour of sows and the biochemical indices of the offspring, and a conclusion on the reproductive performance based on the numbers of sows in the present study could not be drawn. Back fat thickness was measured by ultrasound, which is considered a good measure of sow body condition (Kapell et al, 2009). Chapinal et al (2010) showed there was no significant difference in the back fat depth of sows during pregnancy between the two housing conditions.…”
Section: Discussionmentioning
confidence: 99%